Pengaruh Intensitas Mengakses Akun Komunikasi Dakwah Di Instagram Terhadap Perilaku Imitatif Mahasiswa FISIP Universitas Pancasakti Tegal - Gatha Daffa Wichaksana; Sarwo Edy; Didi Permadi (Pusat Riset dan Inovasi Nasional, 2022)
This research aims to find out how the intensity of using da'wah communication accounts on Instagram has an impact on the imitative behavior of students at the Faculty of Social and Political Sciences, Pancaskti Tegal University consisting of 608 students, researchers will adopt a research sample of 86 students. This research uses quantitative methods by distributing questionnaires via Google-forms and observation. Then, samples were taken by calculating proportional probability using the stratified random-sampling method. Data was collected using a Likert questionnaire to measure the intensity of access to da'wah communication accounts on Instagram and student imitative behavior through five tests, namely the validity test.instrument, reliability test, normality test, coefficient of determination test (R Square), and Pearson product moment test. The research results show that the working hypothesis is accepted, showing a significant relationship between da'wah communication accounts on Instagram and the imitative behavior of FISIP UPS Tegal students. Apart from that, there is a significant correlation between the intensity of access to da'wah communication accounts on Instagram and the imitative behavior of FISIP UPS Tegal students, with a coefficient of 72.7%.